Efficiency convergence properties of Indonesian banks 1992 - 2007 - Tiantian Zhang; Kent Matthews (Cardiff University, Cardiff Business School, 2011)
This paper examines the convergence properties of cost efficiency for Indonesian banks for the period 1992-2007. It employs the Simar and Wilson's (2007) two stage semi-parametric double bootstrap DEA procedure to estimate cost efficiency. Using panel data estimation, the paper examines β-convergence and σ-convergence, to test the speed at which Indonesian banks are converging, towards the best practice and country average. We find evidence that in general the post-crisis structural reform process improved the average level of efficiency and improved the distribution of efficiency across banks significantly. The Asian financial crisis and the structural reform had the effect of slowing the adjustment speed of bank efficiency.
Keywords: G21; G28; 330; Banks; Efficiency; Indonesia; Convergence; Finanzsektor; Bank; Produktivität; Unternehmenserfolg; Wirtschaftliche Anpassung; Indonesien